Active mode locking of quantum cascade lasers in an external ring cavity - D. G. Revin (Nature Portfolio, 2016)
Compact, integrated mode-locked lasers can produce ultrashort pulses of light in the visible and near infrared, but are more difficult to achieve in the mid-infrared. Here, the authors demonstrate active mode locking of an external-cavity quantum cascade laser emitting at 5.2 micrometres at room temperature.